The Effect Of Jigsaw Cooperative Learning Model Aided With Interactive Multimedia Upon Learning Outcome Of On-Guard Position On Pencak Silat Course - I Ketut Sudiana; I Gede Suwiwa (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aimed at analyzing the effect of Jigsaw Cooperative Learning Model aided with interactive multimedia upon learning outcome of on-guard position on the theory and practice of Pencak Silat course. This is a pre-experimental study using one group pretest-posttest design. This study was conducted Sport Hall of Sport and Health Faculty in Jinengdalem Campus. The amount of the sample was 25 students. The variables consisted of independent variable that was the jigsaw cooperative learning model aided with interactive multimedia and the dependent variable was the learning outcome. The data collection technique was performance test of the basic on-guard position of Pencak Silat. Data were analyzed by using nonparametric inferential statistic in form of Wilcoxon Sign Rank Test which was used to analyse the differences of pre-test and post-test scores. The research finding showed that there were significant differences of on-guard position learning outcome on the course theory and practice of Pencak Silat course before and after the implementation of jigsaw cooperative learning model aided with interactive multimedia (Z = 4.378; p = 0.000). Based on the result of Wilcoxon Sign Rank Test/Wilcoxon Match Pair Test, it was found that there was difference of on-guard position on Pencak Silat course before and after the implementation of Jigsaw cooperative learning model assisted with interactive multimedia. The after implementation/posttest mean score was (96.86) higher than before implementation/pre-test mean score (43.93) of Jigsaw cooperative learning model assisted with interactive multimedia.